A Review on The Relationship Variables to Job Design - Thusyanthy, V. (CSC Press (USA), 2014)
Many scholars have indicated that many factors, dimensions, environment, time, etc. are useful to design jobs in organizations. This review explores with the variety of literature support the relationship of variables with respect to job design. To extend and facilitate further studies contextually and empirically, a mind-map is presented to show how these relationship variables relate to job design. This would enhance the studies related to job design in particular.
Keywords: Job Design; Variables; Relationship; Mind-map